Intervención del terapista respiratorio en paciente femenino de 10 años de edad con asma bronquial. - Alvarado Pazmiño, Anthony Francisco (2023)
Asthma is one of the most common chronic diseases in the world, which has a significant impact on society and the health of children and adults. According to the Ministry of Public Health (MSP), it is believed that 125,000 people in Ecuador suffer from bronchial asthma, of which 70% are children and 30% are adults. The present case is based on a 10 year old female patient and after having carried out the assessment, the definitive diagnosis was bronchial asthma. It is concluded that the main triggers of bronchial asthma were cigarette smoke and environmental allergens. Currently there is no cure for bronchial asthma, but the crises in patients with the disease can be controlled. Treatment of these patients is based on the use of bronchodilators and inhaled corticosteroids.